2005
DOI: 10.1159/000082452
|View full text |Cite
|
Sign up to set email alerts
|

Certain Aspects of Bonobo Female Sexual Repertoire Are Related to Urinary Testosterone Metabolite Levels

Abstract: We examined the unknown relationship between testosterone and sexual behaviour in female bonobos (Pan paniscus) on a daily and long-term level. In most animal species, sexual behaviours mainly focus on reproduction. Bonobos, however, also use sexual interactions to a large extent to maintain and restore social relationships. They display an elaborate sexual repertoire that is expressed during fertile as well as non-fertile periods in life and exhibit a high degree of female control over sexual interactions. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…One species that is notable in terms of variability in timing of ovulation in relation to sexual swelling patterns and female reproductive strategies is the bonobo ( Pan paniscus ). To date, only a few studies have measured ovarian hormones in female bonobos, and all were conducted exclusively in captivity [ 51 54 ]. These studies indicated that the variability in the timing of ovulation in relation to sexual swelling patterns in bonobos is considerably higher than in other species, with ovulation sometimes occurring outside the MSP [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…One species that is notable in terms of variability in timing of ovulation in relation to sexual swelling patterns and female reproductive strategies is the bonobo ( Pan paniscus ). To date, only a few studies have measured ovarian hormones in female bonobos, and all were conducted exclusively in captivity [ 51 54 ]. These studies indicated that the variability in the timing of ovulation in relation to sexual swelling patterns in bonobos is considerably higher than in other species, with ovulation sometimes occurring outside the MSP [ 53 ].…”
Section: Introductionmentioning
confidence: 99%